"And it shall come to pass on that day, the Lord will whistle for the fly which is at the end of the water channels of Egypt, and for the bee which is in the land of Assyria" (Is 7:18): Traumatic impact of the Covid-19 virus as a lens to read Isaiah 7:18– - Esterhuizen, Elizabeth (HTS teologiese studies, 2021)
In this article the impact of the Covid-19 virus will be used as a lens to read this Isaianic text. The collective threat of the corona-virus causes trauma on societies and communities on different levels: psychological, physical, existential and communal trauma.Isaiah 7:18–25 also tells us of an historic event which caused extreme trauma to its audience. Verse 18 describes the arrival of the Assyrian army. The prophet compares the Assyrian hosts to the flies “in the rivers of Egypt”, and to the bees in Assyria; that is to say, the invaders will be the innumerable and speedy warriors of the Assyrian king. This portrayal is expanded stating that the flies and the bees will swarm all over the land, penetrate every corner and crack and it will be impossible to get rid of them. The plague of “flies” in the metaphor represents the large numbers, while the “bees” are clearly the aggressive and terrifying ones in this metaphor. Just as the Assyrians, who are about to appear as an unwanted and troublesome multitude of flies and bees from which Ahaz will be unable to free himself and his kingdom, the Covid-19 virus is causing havoc and wreckage to societies all over the world.Contribution: This article reflects theologically on the immense psychological and existential damage of trauma caused by the terrifying and laming fear this virus has on the mental well-being of a society. The theological reflections will engage with a biblical text which also reflects on the traumatic effects of threat and fear that lamed a society.